Experimental findings on God as an attachment figure normative processes and moderating effects of internal working models. [article]. - Grangvist, Pehr
Four studies examine implications of attachment theory for psychological aspects of religion among Israeli Jews. Study 1 replicated previous correlational findings indicating correspondence among intern-personal attachment orientations, attachment to God, and image of God. Studies 2-4 were subliminal priming experiments, which documented both normative and individual-difference effects. Regarding normative effects, findings indicated that threat priming heightened cognitive access to God-related concepts in a lexical decision task (Study 2); priming with "God" heightened cognitive access to positive, secure base-related concepts in the same task (Study 3); and priming with a religious symbol caused neutral material to be better liked (Study 4). Regarding individual differences, interpersonal attachment related avoidance reduced the normative effects (i.e., avoidant participants had lower implicit access to God as a safe haven and secure base). Findings were mostly independent of level of religiousness. The present experiments considerably extend the psychological literature on connection between attachment constructs and aspects of religion. - (from the authors)